In situ synthesis of Ni/NiO composites with defect-rich ultrathin nanosheets for highly efficient biomass-derivative selective hydrogenation. Issue 30 (2nd July 2019) - Wang, Yunan; Cao, Feng; Lin, Weiwei; Zhao, Fengyu; Zhou, Jun; Li, Song; Qin, Gaowu
Abstract : Synergism of geometric construction and electronic regulation: numerous Ni nanoparticles combined with defect-rich ultrathin NiO nanosheets for efficient hydrogenation. Abstract : Herein, a Ni/NiO composite catalyst was synthesized by a simple in situ reduction method, and its catalytic hydrogenation performance has been verified to be superior to that of noble metals. In particular, the catalysts can transform 2(5 H )-furanone (HFO) to γ-butyrolactone (GBL) efficiently under mild conditions, which effectively upgrades the biomass-derivatives. The superior catalytic activity can be attributed to the synergism of the geometric construction and electronic regulation. Specifically, ultrathin NiO nanosheets contain plenty of surface defects and relatively large mesopores. Those defects can be helpful in the activation and dissociation of hydrogen, the adsorption of HFO molecules, as well as the enhancement of the local hydrogen concentration on the catalyst, while the pores can be considered as nano-reactors for hydrogenation. The strong interaction at the interface caused by the in situ synthesis can further tune its electronic structure and improve the hydrogen adsorption. In addition, the catalyst also displays great catalytic properties for p -nitrophenol (PNP) hydrogenation and non-enzymatic glucose sensing, which further supports the promising application potential of such catalysts with the unique mesostructures of Ni/NiO heterojunctions with defect-rich ultrathin nanosheets.